USE OF COMMUNICATIVE LANGUAGE TEACHING METHOD FOR STUDENTS AT STMIK ROYAL IN KISARAN - Cecep Maulana (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2019)
The main purpose of this study is to know the improvement of teaching English speaking by using Communicative Language Teaching method for students at the STMIK Royal Teladan Kisaran. The method of  this research is classroom action research (CAR). The data in this research is used percentages analysis. The respondents of this research for students at the STMIK Royal Teladan Kisaran which consist of  20 students. Based on result of data analysis there are improvements on students’ speaking achievement in each cycle. The data shows 4 cycles in this learning activity for students to know something about the students’ speaking achievement. The result shows that the students’ speaking achievement is 23% (excellent), 50% (very good), 27% (good), 0% (low) and 0% (failed). This research indicates that the using of Communicative Language Teaching method can improve students’ speaking achievement at the STMIK Royal Teladan Kisaran